Sustainable Materials Enabled Terahertz Functional Devices - Wang, Baoning; Wang, Haolan; Bao, Ying; Ahmad, Waqas; Geng, Wenhui; Ying, Yibin; Xu, Wendao (Nano-Micro Letters, 2025)
Terahertz (THz) devices, owing to their distinctive optical properties, have achieved myriad applications in diverse domains including wireless communication, medical imaging therapy, hazardous substance detection, and environmental governance. Concurrently, to mitigate the environmental impact of electronic waste generated by traditional materials, sustainable materials-based THz functional devices are being explored for further research by taking advantages of their eco-friendliness, cost-effective, enhanced safety, robust biodegradability and biocompatibility. This review focuses on the origins and distinctive biological structures of sustainable materials as well as succinctly elucidates the latest applications in THz functional device fabrication, including wireless communication devices, macromolecule detection sensors, environment monitoring sensors, and biomedical therapeutic devices. We further highlight recent applications of sustainable materials-based THz functional devices in hazardous substance detection, protein-based macromolecule detection, and environmental monitoring. Besides, this review explores the developmental prospects of integrating sustainable materials with THz functional devices, presenting their potential applications in the future. Highlights: 1 Sources and types of sustainable materials and their advantages in fabricating high performance terahertz (THz) functional devices are systematically reviewed. 2 The principles and implementations of sustainable material enabled THz functional devices for wireless communication, molecular sensing, and biomedical detection. 3 This review emphasizes new insights from a comprehensive analysis, presenting challenges in intelligent modulation and perception of sustainable materials assisted THz functional devices.